Strategy Formulation to Increase the Passengers of Singapore Airlines - Pramitha, Dewi Ayu; Wasito, Tito; Ozali, Imam (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2018)
Singapore airlines is the one of airlines which is still peopleâs choice to be the airline that make them easy to reach their destination butÂ  business competition in the aviation industry very tight, this situation obviously make the passenger volume is declining. The purpose of this research are (a) To analyze the internal factors (strengths and weakness),(b) To analyze the external factors (opportunities and threats), (c) To determine the position of the companyâs on the matrix IE, diagram SWOT and the matrix TOWS or SWOT, (d) To determine the strategies to increase sales of seats . Research method using qualitative method with survey and SWOT Analysis as tools.Â  Based on IE Matrix this company be in a position relatively excellent and then on the result of diagram SWOT is in the Quadrant I which means the company is in an aggressive position, so that it can be concluded that the strategy used for the SWOT Matrix is SO strategy, which is use the strength to take advantage of opportunity that owned by the company. From the calculation results using a variety of analysis tools, the suitable alternative strategy for this company is market penetration and product development.